Dysregulation of protein phosphatase 2A in parkinson disease and dementia with lewy bodies. Issue 10 (7th September 2016) - Park, Hye‐Jin; Lee, Kang‐Woo; Park, Eun S.; Oh, Stephanie; Yan, Run; Zhang, Jie; Beach, Thomas G.; Adler, Charles H.; Voronkov, Michael; Braithwaite, Steven P.; Stock, Jeffry B.; Mouradian, M. Maral
Abstract: Objective: Protein phosphatase 2A (PP2A) is a heterotrimeric holoenzyme composed of a catalytic C subunit, a structural A subunit, and one of several regulatory B subunits that confer substrate specificity. The assembly and activity of PP2A are regulated by reversible methylation of the C subunit. α ‐Synuclein, which aggregates in Parkinson disease (PD) and dementia with Lewy bodies (DLB), is phosphorylated at Ser129, and PP2A containing a B55 α subunit is a major phospho‐Ser129 phosphatase. The objective of this study was to investigate PP2A in α ‐synucleinopathies. Methods: We compared the state of PP2A methylation, as well as the expression of its methylating enzyme, leucine carboxyl methyltransferase (LCMT‐1), and demethylating enzyme, protein phosphatase methylesterase (PME‐1), in postmortem brains from PD and DLB cases as well as age‐matched Controls. Immunohistochemical studies and quantitative image analysis were employed. Results: LCMT‐1 was significantly reduced in the substantia nigra (SN) and frontal cortex in both PD and DLB. PME‐1, on the other hand, was elevated in the PD SN. In concert with these changes, the ratio of methylated PP2A to demethylated PP2A was markedly decreased in PD and DLB brains in both SN and frontal cortex. No changes in total PP2A or total B55 α subunit were detected. Interpretation: These findings support the hypothesis that PP2A dysregulation in α ‐synucleinopathies may contribute to the accumulation of hyperphosphorylated α ‐synuclein and to the disease process, raising the possibility that pharmacological means to enhance PP2A phosphatase activity may be a useful disease‐modifying therapeutic approach.